PENGARUH KOMPETENSI, INDEPENDENSI, DAN PROFESIONALISME TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (FRAUD) - Marcellina Widiyastuti; Sugeng Pamudji (Value Added : Majalah Ekonomi dan Bisnis, 2009)
This study aims to examine the influence of competency, independency, and professionalism toward auditor's ability to detect fraud This study uses competency, independency, and professionalism because these are auditor's minimum attitudes that must auditors have in their tasks. Using questioner to collect data to auditor who works in Badan Pemeriksa Keuangan Republik Indonesia (The Indonesia's Supreme Audit Institution), Jakarta. This research use purposive sampling to choose the sample. From 93 questionnairs, only 68 questionnairs were back. In this study, researcher used Partial Least Square (PLS) with SmartPLS software. The result indicates that competency, independency, and professionalism have significantly and positively effict toward auditor's ability to detect fraud. This result also indicates that there is no differently from competency, independency, and professionalism between independent auditor and governmental auditor toward auditor's ability to detect fraud.  Future research is expected can extend survey area coverage, variables research object, and don't spread the questionnairs in audit times. Keyword:      competency, independency, and professionalism toward auditor's ability to detect fraud